Effect of bone morphogenetic protein 2 (bmp-2) on the expression of mesenchymal stem cells and cancer stem cell surface markers - Zulkifli, Nur Sufiah; Ab-Rahim, Sharaniza,; Muhamad, Mudiana (Research and Innovation Division, Universiti Teknologi MARA (UiTM) Selangor, 2025)
Mesenchymal stem cells (MSCs) are recognized for promoting cancer cell proliferation, angiogenesis, and metastasis. Modification of tumour microenvironment (TME) is attributable to the cancer stem cell (CSC) population recruiting and activating specific cell types such as MSCs. Bone morphogenetic protein-2 (BMP-2) has a modulatory role towards TME via cytokines action, which may affect MSCs differentiation into CSCs. However, the cellular molecular mechanism involved remains elusive. Therefore, this study aims to investigate the expression of CSC population in the human umbilical mesenchymal stem cell (hUCMSC) that was treated with BMP-2. The hUCMSC were cultured in Dulbecco’s Modified Eagle Medium F-12 (DMEM/F-12), 10% foetal bovine serum (FBS) and 1% penicillin-streptomycin at 370C in a humidified incubator of 5% CO2. The stem cell properties were analysed via flowcytometry analysis of stem cell surface markers; CD105, CD90, CD73, and CD34. Prior to treatment of the hUCMSC, cytotoxicity analysis of BMP-2 was carried out with different concentrations of 0.05, 0.10, 0.15, 0.20, 0.25, 0.30 μg/ml incubated for 8, 16 and 24 hours. Post-treated hUCMSC was analysed for the expression of cancer stem cell surface marker CD133. Flow cytometry result showed high expression levels of both positive and negative stem cell markers; CD105+, CD90+, CD73+ and CD34-, indicating presence of stem cell populations in the hUCMSC. Meanwhile, treatment with 0.05 μg/mL of BMP-2 for 24 hours presented the highest number of viable cells at 80%, hence was used for treatment of the hUCMSC. Unfortunately, expression of CD133 was absent in the BMP-2 post-treated hUCMSC, indicating lack of CSC differentiation. In conclusion, although BMP-2 was ineffective towards CSC progression, its role towards stem cell differentiation into CSC remains elusive since results of this current study are still preliminary, and thus require further investigations